(untitled) (Marketing Journal, 2025)
This article analyzed the impact of the automotive industry on the national economy of the Republic of Uzbekistan. Based on official statistical data, the study assessed changes in automobile production volumes during 2019 –2024, as well as the sector’s con tribution to gross domestic product and employment. The role of the automotive industry in export activities and its economic impact on related sectors, including metallurgy, logistics, and services, were examined. The analysis revealed that growth in prod uction volumes was associated with increased investment and expansion of production capacities. The findings confirmed that the automotive № 1 620 industry has become one of the steadily developing and significant sectors of the national economy.